Comparison of the Effectiveness of Couple Therapy in the Way of Psychodrama and Integrative Behavioral Couple Therapy (IBCT) on Improving Conflict Resolution Tactics in Contradictory Couples - Mozhgani , Paria; Moradi , Omid; Ahmadian , Hamzeh; Yarahmadi , Yahya (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of the present study was to compare the effectiveness of Psychodrama Couple Therapy and Integrated Behavioral Couple Therapy (IBCT) on improving conflict resolution tactics of contradictory couples. Method: The method of this semi-experimental study is pre-test/post-test with a control group and a follow-up phase. The statistical population included all conflicting couples who referred to Dramatherapy Center of Iran in 2019. The sample of this study includes 36 persons (18 couples) who referred to Dramatherapy Center of Iran who were selected by the available sampling method. Then they were assigned in 3 groups of 12 persons including two experimental groups and one control group. The first experimental group underwent 12 sessions of Psychodrama Couple Therapy by Moreno (1969) and the second experimental group underwent 12 sessions of Integrative Behavioral Couple Therapy by Christensen et al. (2014). Data were obtained by using Conflict Tactics Scale (CTS2) by Straus (1996) and analyzed by methods of repeated measure analysis of variance using spss22 software. Results: The results of this study showed that Psychodrama Couple Therapy reduced physical assault (F=11.52 and p=0.001) and psychological violence (F=12.74 and p=0.001) and increased non-violent negotiation (F=58.84 and p=0.001) in the victim form and respectively physical assault (F=17.96 and p=0.001), psychological violence (F=17.08 and p=0.001) and non-violent negotiation (F=89.45 and p=0.001) in the aggressive form. Conclusion: The results indicated the effectiveness of Psychodrama Couple Therapy on reducing physical assault and psychological violence and increasing non-violent negotiation in conflicting couples and its durability over time. Therefore, health professionals and therapists can use Psychodrama Couple Therapy along with other treatment methods to improve couples' conflict resolution tactics.